KOMBINASI METODE ACOUNT UNTUK PENURUNAN NYERI PERSALINAN - -, Nasriyah; Nisak, Ana Zumrotun (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Background: Childbirth is a natural process that feels by every pregnant woman. The labor process is not same. Sometimes the labor process needs a long time and causes pain. The conditions of severe pain in the first stage of labor encourage the mothers to chose the easiest way and quickly to relieve pain through caesarean operation even without a clear indication. One of the ways to handle the labor pain with non-pharmacological techniques is by using acupressure and counter pressure. The combinations of these two methods aim to obtain better results in the reduction of labor pain in the active phase of the first stage of maternity. Objective: This study amis to identify the effectiveness of the combination between acupressure and counter pressure on the first stage of labor pain reduction in the active phase of normal deliveries. Method: The design of this study using quasi-experimental design with pre-post test. This approach is used to look at the effectiveness of treatment through the differences between the groups before and after treatment, and then observed. The population in this study was all mothers who included in the criteria for inclusion and exclusion in BPM which will be used as a place of research. The sample in this study was normal birth mothers, 36 respondents. The sampling technique in this research used consecutive sampling. Moreover, the analysis of the data was Wilcoxon. Results: The study showed that there is no significant difference before and after treatment using the method of Acount, with p = 0.000 (p <0.05). Conclusion: In this study, the combination of Acount methods is highly effective in reducing labor pain active phase of the first stageKeywords: Methods acount, labor pain